Audio described comics in the museum - Asimakoulas, Dimitris (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
Audio Description is typically used to describe the visual aspects of various cultural products in the creative industries: performed plays, films, sports matches, art gallery and museum items. Such descriptions offer alternative sensory input for blind or partially sighted audiences and have been the staple of research in Audiovisual Translation Studies. There are, however, rather few studies focusing on museum environments and none that examine the niche area of comic art. This article addresses such a gap in two ways. First, it explores comics from an audiovisual translation/accessibility perspective. Second, it reports findings from a pilot study of accessible comic art where the views of selected professionals (curator, comic artists, audio describer) were collected, descriptions for three comics were commissioned and the responses of blind visitors to a comic art museum were gauged. The audio described comics—not without their limitations, as will be shown—are the result of a contingent collaboration of actors in the space of the museum.